Autonomous Three-Phase Induction Generator Supplying Unbalanced Loads - ION, C. P.; MARINESCU, C. (Universitatea Stefan cel Mare din Suceava, 2013)
This paper presents a control method for a stand-alone micro hydro with induction generator (IG) supplying unbalanced three-phase loads. Besides voltage and frequency regulation, the phase balancing is ensured for this particular operating regime. The proposed control topology relies on a combination between a voltage source inverter (VSI) and a dump load (DL). The VSI imposes the system frequency and performs the unbalances compensation, while the DL deals with the voltage regulation. Experiments have yielded the reliability of this configuration during generator loading and unbalanced loads supply.